Efficacy of intravenous immunoglobulin monotherapy in patients with cutaneous lupus erythematosus: results of proof-of-concept study (Dermatology Reports, 2015)
Cutaneous lupus erythematosus (CLE) is a chronic inflammatory autoimmune skin disease. Evidence-based therapy for CLE is lacking in the most part. Intravenous immunoglobulin (IVIg) is being increasingly utilized as off-label therapy for a variety of autoimmune and inflammatory conditions, especially in dermatology. The usefulness of IVIg in CLE is not well established. The goal of the present study was to obtain the proof-of-concept evidence that IVIg can control acute CLE and thus replace current systemic immunosuppressive therapy that causes severe side effects and adverse reactions. Sixteen patients who tried and failed various systemic treatments for CLE were screened and consented to use IVIg as a monotherapy. The IVIg was administered at 500 mg/kg/day on 4 consecutive days up to a total of 2 g/kg/month for 3 months, and the subjects were monitored for additional 6 months off any drug for a possible relapse. The cumulative results revealed an overall improvement, as evinced by a decrease of both objective and subjective measures of disease activity. The most sensitive and specific objective and subjective instruments for assessment of the therapeutic effect of IVIg were CLASI-A (Cutaneous Lupus Erythematosus Disease Area and Severity Index) measuring disease activity and Skindex-29 scores, respectively. The CLASI-A score dropped down from the initial value taken as 100%, and remained in the range of approximately 70% until the last visit. Three patients (18.8%) had a temporary flare of CLE symptoms but recovered within a month from the relapse. No serious side effects and adverse reactions occurred. Thus, IVIg monotherapy in CLE allowed to achieve: i) rapid and persistent decreased in disease activity; ii) steady improvement of patients’ quality of life assessed by Skindex-29; iii) low relapse rate; and iv) mild nature and short duration of relapses. Since healing was maintained for months after IVIg treatment, it is possible that the IVIg-triggered molecular events mediating the therapeutic action of IVIg that continued to unfold after the end of therapy.